The Birth of a Novella: On Lyra and the Creative Writing Process - Steinunn Brynja Óðinsdóttir 1993- (2017)
This essay is written as a B.A. thesis for the University of Iceland and explores the process of creative writing. It consists of two parts. The first part is a novella, Lyra, which is about a twenty-three year old girl named Lyra. When we first meet Lyra in the novella she is sitting at the top of a very tall building in Vancouver, Canada, having trouble deciding whether she should jump or not. The novella focuses on major events in her life including her battle with anorexia, her stay at an inpatient eating disorder treatment clinic and how she tries to cope with the death of her girlfriend, Claire. Lyra, who is living in Miami, Florida, when her girlfriend commits suicide, decides to move back to her hometown in Canada. She wants get as far away from her ignorant mother and the man who she refuses to call her stepfather as she can. But moving to Canada does not make living without the love of her life any easier and her internship at The Northern Star does not live up to her expectations. Lyra has to decide whether life is worth living without Claire and if she is capable of living a normal life without her. The second part is an exposition on the writing process. It explores where the best ideas usually come from, how they transform during the creative writing process and how an author can use his or her own experience and others to create fiction. It also explains where the idea for this particular novella came from and how it developed. It discusses the main elements of a story such as plot, setting, narration and characters. At last it touches on the subject of writer’s block and any roadblocks an author may encounter and how to solve them.